1992
DOI: 10.1073/pnas.89.7.2965
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations of the epidermal growth factor receptor gene in human gliomas.

Abstract: The epidermal growth factor receptor (EGFR) gene is amplified in 40% of lignant gliomas, and the amplified genes are frequently rearranged. We have characterized the genetic alterations asoated with these rearrangements in five malignant gliomas. In one tumor the rearrangement resulted in the deletion of most of the extracytoplasmic domain of the receptor, resulting in a hybrid mRNA between new sequences and the truncated EGFR sequence. The predicted amino acid sequence of the protein from this tumor was remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
504
1
9

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 757 publications
(520 citation statements)
references
References 23 publications
3
504
1
9
Order By: Relevance
“…19 --21 A common example of abnormal RTK activation is the epidermal growth factor receptor class III variant, which is present in a substantial proportion of malignant gliomas and other human cancers, but completely absent in normal tissues. 22,23 This variant results from a transcript having an 801-bp in-frame deletion of EGFR that corresponds to exons 2 --7, which leads to the generation of a protein with a truncated extracellular domain. 21,24 Several molecular mechanisms have been implicated in the oncogenic pathway with epidermal growth factor receptor class III variant downstream signaling.…”
Section: Discussionmentioning
confidence: 99%
“…19 --21 A common example of abnormal RTK activation is the epidermal growth factor receptor class III variant, which is present in a substantial proportion of malignant gliomas and other human cancers, but completely absent in normal tissues. 22,23 This variant results from a transcript having an 801-bp in-frame deletion of EGFR that corresponds to exons 2 --7, which leads to the generation of a protein with a truncated extracellular domain. 21,24 Several molecular mechanisms have been implicated in the oncogenic pathway with epidermal growth factor receptor class III variant downstream signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of EGFR has been observed in both premalignant lesions and malignant tumors of the lung, and occurs in 40-80% of patients with NSCLC (Salomon et al, 1995;Grandis and Sok, 2004;Merrick et al, 2006). EGFR overexpression was suggested to result primarily from epigenetic causes, including transcriptional activation; however, gene amplification and oncogenic viruses can also have an important function (Wong et al, 1992;Rubin Grandis et al, 1996a, b;Grandis and Sok, 2004). In tumors, the EGFR signaling network can result in the activation of MAPK, PLCg, PI3K/AKT, the STAT transcription factors, proto-oncogene transcription factors, such as fos, jun and myc, and zinc-finger-containing transcription factors, such as Sp1 and Egr1 (Grandis and Sok, 2004).…”
Section: Egfr and Her2 Overexpressionmentioning
confidence: 99%
“…Oncogenic Ras mutations have not been discovered in human astrocytomas (Bos, 1989;Tuzi et al, 1991), which constitute the most common primary malignancy involving the central nervous system (Zimmerman, 1969). However, it has been demonstrated that high grade (grade IV) astrocytomas, known as glioblastoma multiforme (GBM), express high levels of ligand-dependent and -independent growth factor receptors (Fleming et al, 1992;Guha et al, 1995a;Libermann et al, 1984;Niste r et al, 1988;Steck et al, 1988;Sugawa et al, 1990;Wong et al, 1992) which are functionally relevant for tumour growth (Guha et al, 1995a,b;Shamah et al, 1993). We have demonstrated these various receptors to result in a functional activation of the Ras pathway in a wide range of astrocytoma cell lines (U87, U118, U138, U343 and U373-MG cells).…”
Section: Introductionmentioning
confidence: 99%